The Effect of Tool Path Strategy on Twist Behavior In Single Point Incremental Sheet Metal Forming (Journal of Engineering, 2013)
In Incremental sheet metal forming process, one important step is to produce tool path, an accurate tool path is one of the main challenge of incremental sheet metal forming process. Various factors should be considered prior to generation of the tool path i.e. mechanical properties of sheet metal, the holding mechanism, tool speed, feed rate and tool size. In this work investigation studies have been carried out to find the different tool path strategies to control the twist effect in the final product manufactured by single point incremental sheet metal forming (SPIF), an adaptive tool path strategy was proposed and examined for several Aluminum conical models. The comparison of the proposed tool path with the conventional iso planar and helical tool paths shows that there is no effect of twisting in the final model when using adaptive tool path, while the twisting effect are clearly observed and measured in the final product when using both iso planar and helical tool path When forming 80 and 110mm depth conical cup. The time of forming has been measured and its observed that in adaptive tool path the time of forming is less than 8.7 %from the helical tool path when forming conical cup with 50mm depth and less than of 8.91% when forming conical cup with 110mm depth